TINJAUAN SJSN KESEHATAN DENGAN PELAYANAN DOKTER KELUARGA - Widi, Raharjo (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2014)
National Social Assurance System (NSAS) has been valid from January 1, 2014 , with PT.ASKES as the Health Social Assurance Agency. The Preparation to welcome the validity of the National Social Assurance System (NSAS) has been doing. Until now the regulation of laws has not come yet to the procedures and technical guidelines. The health services on NSAS primary physician that is comprehensive became a choice by applying the pattern of health care family physician. Based on the regulation of laws, reference books, seminar materials and especially experience as a general practice physician who served patients with pre-paid system for almost 15 years, providing input like problems that can arise and the alternative solutions in order to support NSAS work better, maintained the quality and continuity, seeking the least possible service problems especially on the family physician service